Pengembangan Media Audio Visual untuk Menigkatkan Minat Belajar Siswa pada Pelajaran PDTO di SMK Kelas X - Aci Primartadi; Widiyatmoko Widiyatmoko; Hafid Nur Rahman; Ponco Susilo; Thauva Hidayatullah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to (1) determine the feasibility of Audio Visual-based learning media in the subject of Basic Automotive Engineering Works (PDTO) at SMK Negeri 8 Purworejo, (2) to determine the increase in learning interest of class X TBSM students at SMK Negeri 8 Purworejo after using Audio Visual-based learning media. The data collection technique in this study was by distributing questionnaires. This study used the Research and Development (R & D) method with the research subjects taken being class X TBSM students at SMK Negeri 8 Purworejo totaling 36 students. The results showed a difference in learning interest in students at SMK Negeri 8 Purworejo between classes that did not use audio visual media and classes that used audio visual media for the subject of Basic Automotive Engineering Works (PDTO), namely a percentage of 73.33 was obtained and in the second data collection or research using audio visual learning media, a percentage of 86.38 was obtained, there was a significant increase of 13.05. From the increase in learning interest, it can be concluded that using audio-visual learning media can increase students' learning interest, especially in the subject of Basic Automotive Engineering Work, basic competency of mechanical measuring instruments.